Alternative technique of cervical spinal stabilization employing lateral mass plate and screw and intra-articular spacer fixation - Goel, Atul (Medknow Publications & Media Pvt Ltd, 2013)
AIM: The author discusses an alternative technique of segmental cervical spinal fixation. MATERIAL AND METHODS: The subtleties of the technique are discussed on the basis of experience with 3 cases with a follow-up of between 30 and 36 months. TECHNIQUE: The technique involves debridement of facetal articular cartilage, distraction of facets, jamming of ‘Goel spacer’ into the articular cavity and fortification of the fixation by lateral mass plate and screw fixation. The ‘double-insurance’ method of fixation is safe for vertebral artery, nerve roots and spinal neural structures and the fixation is strong. CONCLUSIONS: The discussed technique is safe and provides a strong fixation and a ground for ultimate arthrodesis.